Evaluating The Practice Of Teaching /Learning Integrated Language Skills In English Language Classroom: The Case Of Liben Mecha Secondary School, Grade Ten Students - Abera Abdeta (My University, 2017)
This research was conducted to evaluate the practice of teaching/learning integrated language skills at grade 10 level. Liben Mecha Secondary School has been the center of the study. The study employed descriptive research design and mixed approach for data collection. Ten English teachers were selected using available sampling technique and one hundred eight students were randomly selected from grade ten for the study. In order to collect data from the participants, three data collection instruments were employed: questionnaire, structured observation and interview. 30 questions were prepared and administered to ten teachers. The teachers were also interviewed after 8 interview questions were designed 25 questions were prepared and distributed to 108 students at random from all sections and also interview was conducted by using simple random sampling. Classroom observation was made by simple random selection in four classes three times each. Questionnaire data were tabulated and analyzed quantitatively by using frequency and percentage. Interview data were transcribed qualitatively then analyzed by verbal description. The study showed that, in relation to integrated skills both teachers and students had positive attitudes but they were impractical. That is to say, the teachers didn’t use strategies like designing authentic and relevant tasks, promoting peer evaluation except for providing receptive skills activity as an input for productive skills. Even though students perceive the approach positively, they remain in passive integrated language class because L2 anxiety and lack of practice, shortage of time, lack of interest and effort to participate in teaching/learning process of language skills, students’ lack of language proficiency and large class size were the major factors affecting teaching/learning integrated language skills revealed by the findings. This shows that there are gaps between teachers’ perception and their practice .It was recommended that, for effective implementation of integrated skills teachers and students should play their roles properly in the classroom, all the stakeholders are required to provide necessary resources and efforts to overcome the problem.
The Case Of Liben Mecha Secondary School, Grade Ten Students